Implementasi Konseling Eksistensial Humanistik untuk Menurunkan Kecemasan Kematian pada Mahasiswa - Damayanti, Devi; Tirtasari, Nilam Anggieta; Saraswati, Aulia Rizkika; Shakila, Disma Nadya; Santiko, Pribadi Wahyu; Efendi, Muhammad Yunus; Nuryono, Wiryo; Ratnasari, Devi (Jurnal Bimbingan dan Konseling Pandohop, 2025)
Death anxiety is a form of existential anxiety that can disrupt an individual's emotional balance and daily functioning, particularly among university students who are navigating developmental and personal challenges. This study aims to examine the effectiveness of the humanistic-existential counseling approach in helping students cope with death-related anxiety. A qualitative case study method was employed, involving five individual counseling sessions with a student experiencing intense anxiety following the loss of a parent. The results show that existential counseling helped the counselee reflect on traumatic experiences, understand the root causes of their anxiety, and reconstruct the meaning of life. The counselee demonstrated improvements in self-awareness, acceptance of existential reality, and the ability to manage negative thoughts in a more adaptive way. This study concludes that humanistic-existential counseling is effective in reducing death anxiety by guiding counselees to discover personal meaning, embrace freedom of choice, and take responsibility for their lives.